2012
DOI: 10.1007/s00391-012-0326-2
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative cognitive dysfunction in geriatric patients

Abstract: Postoperative cognitive dysfunction (POCD) is a severe long-term complication after surgical procedures. POCD is mainly seen among geriatric patients. Hospitalization, extent of surgery, and systemic inflammatory response might contribute to POCD. The possible influence of the type of anesthesia is discussed. POCD is often not recognized; thus, incidence rates are likely to be underestimated (19-40%). POCD is associated with major consequences for the individual patient, e.g., delayed long-term recovery, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 41 publications
0
25
1
1
Order By: Relevance
“…Some studies also find that lower educational level is associated with increased risk of POCD [51,52]. However, we did not find these associations in the present study.…”
Section: Discussioncontrasting
confidence: 98%
“…Some studies also find that lower educational level is associated with increased risk of POCD [51,52]. However, we did not find these associations in the present study.…”
Section: Discussioncontrasting
confidence: 98%
“…POCD, a decline in cognitive function following surgery, is commonly observed in elderly patients (11). It has been demonstrated that extracts from Polygala tenuifolia root are able to promote memory in healthy individuals and enhance cognitive functions in elderly patients (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures and administration of anesthesia are associated with a transient or permanent decline in cognitive function, termed postoperative cognitive dysfunction (POCD). POCD delays rehabilitation and increases morbidity and early mortality [5] , and also has emerged as a major health concern, especially in the geriatric population [6] .…”
Section: Introductionmentioning
confidence: 99%